3416 Building Resilience & Wisdom in Clinical and Translational Researchers: A Mixed-Method Study of a Pilot Curricular Intervention - Burks, Sandra (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: The clinical and translational research workforce is in jeopardy due to investigator attrition and competing demands upon researchers. Resilience and wisdom are measurable traits that can be acquired. The aim of this study was to examine a pilot curricular intervention promoting resilience and wisdom formation in early-career translational researchers. METHODS/STUDY POPULATION: We conducted a prospective, mixed-methods evaluation of a curricular intervention promoting the development of wisdom and resilience among junior faculty in a career development program. Six 90 minute sessions were delivered between September 2017 and January 2018. Pre- and post- resilience and wisdom were measured using the Connor Davidson Resilience Scale and 3D-Wisdom Scale. Individual semi-structured interviews were conducted before and after the intervention RESULTS/ANTICIPATED RESULTS: Five scholars participated. Median resilience and wisdom scores revealed moderate levels of each trait; pre- and post-scores were not significantly different. Four themes emerged from the analysis of interview transcripts: 1. “Success” broadly defined; 2. Adversity threatens success; 3. Community breeds resilience; and 4. Wisdom formation parallels growth towards independence. DISCUSSION/SIGNIFICANCE OF IMPACT: An intervention aimed at developing capacities of resilience and wisdom is feasibly delivered to early career researchers. The relationship between these capacities and the sustainability of a research career warrants additional study.